Vaccines from the Spanish Influenza as a firm foundation for new developments - John S. Oxford; Douglas Gill (Taylor & Francis Group, 2020)
In 1914, the concept of a prophylactic vaccine, administered to a person before the disease had been contracted, was still controversial. Nevertheless, Almroth Wright tested new pneumococcus vaccines in South Africa, where the incidence of bacterial pneumonia was high amongst workers in the gold mines. He established the use of clinical trials, using around ten thousand workers, both in vaccinated and unvaccinated groups. The two groups were not matched to modern standards. Also, of course, those workers in the control unvaccinated group could not be protected: but some considered a prophylactic vaccine would exacerbate the disease. The vaccines were manufactured to contain a range of pneumococci from different clinical samples, in a serious attempt to match the microbes in the vaccine to the field bacteria. Deaths were averted by the vaccine; and side effects were noted to be minimal. Reexamination of pathology samples from the Spanish Influenza Pandemic showed quite clearly the contribution of pneumococci and streptococci to the mortality of over fifty million people in 1918-1919. The microbe causing this Pandemic was isolated in 1933, and was shown to be a true virus; this finding initiated a huge expanse and interest in influenza virus vaccines, both killed and live. A chance discovery allowed the purification of Influenza M and NP proteins then permitted the production of experimental vaccines. These vaccines were formulated to induce and B and/or T cell responses to the internal proteins. Several of these Universal Influenza Vaccines have been tested in quarantine, and have now reached Phase III trials in the community.